The shark panel: An InDel multiplex for shark species identification. (December 2015) - Amaral, C.R.L.; Pereira, F.; Loiola, S.; Silva, D.A.; Amorim, A.; Carvalho, E.F.
Abstract: The Elasmobranchii comprises the diverse and important group of sharks and rays. The Selachii or sharks clade includes some of the ocean's largest predatory fishes, being commercially overexploited due to unsustainable fishing activities for their meat and fins. Overfishing has resulted in significant population declines and several Selachii species are now considered under high threat and facing extinction, with about 93% of its nominal species included in the IUCN Red List. Molecular data has provided important information about these species, allowing the management of natural stocks and their decline. Population genetics, connectivity data, and their population genetics knowledge are now available and play an important role on establishing conservation policies. However, despite the ecological, commercial and conservation importance, no molecular method is available to identify sharks in a forensic analytic context. As a first step in the construction of a reliable method for shark identification, we carried out a molecular systematic analysis using 85 previously published mitochondrial 16S rRNA gene sequences obtained from the NCBI database. We found that indels in the 16S rRNA gene can be used to distinguish almost all the analyzed shark species, including some of the most threatened according to IUCN Red List. The regions selected in this study can be used for the construction of molecular assays for shark identification in a forensic context.